2017
DOI: 10.1155/2017/4397028
|View full text |Cite
|
Sign up to set email alerts
|

Salt, Aldosterone, and Parathyroid Hormone: What Is the Relevance for Organ Damage?

Abstract: Structured interventions on lifestyle have been suggested as a cost-effective strategy for prevention of cardiovascular disease. Epidemiologic studies demonstrate that dietary salt restriction effectively decreases blood pressure, but its influence on cardiovascular morbidity and mortality is still under debate. Evidence gathered from studies conducted in patients with primary aldosteronism, essential hypertension, or heart failure demonstrates that long-term exposure to elevated aldosterone results in cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 76 publications
(85 reference statements)
1
5
1
2
Order By: Relevance
“…This observation contradicts the findings of a meta-analysis, which showed that blood pressure is negatively associated with BMD and positively with increased risk of osteoporosis [40]. It is generally agreed that high blood pressure increases the excretion of calcium, thus elevating parathyroid hormone level and bone resorption [9]. We suggest that increased systolic blood pressure is reflective of increased body size, which increases the peripheral resistance of the vascular system [41], thus explaining the positive association with BMD.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…This observation contradicts the findings of a meta-analysis, which showed that blood pressure is negatively associated with BMD and positively with increased risk of osteoporosis [40]. It is generally agreed that high blood pressure increases the excretion of calcium, thus elevating parathyroid hormone level and bone resorption [9]. We suggest that increased systolic blood pressure is reflective of increased body size, which increases the peripheral resistance of the vascular system [41], thus explaining the positive association with BMD.…”
Section: Discussioncontrasting
confidence: 71%
“…Diabetes and obesity are associated with bone marrow adipogenesis which deprives mesenchymal stem cells available for osteoblast formation 7 . Hypertension increases excretion of calcium, elevating parathyroid secretion and bone resorption 9 . Oxidized low-density lipoprotein cholesterol particles and excess free fatty acids in dyslipidaemia can uncouple bone remodelling 10 - 13 , favouring bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…A bidirectional stimulating relationship between PTH and aldosterone is reported. Patients with primary aldosteronism have high levels of PTH that return to physiological concentration after the adenoma removal or pharmacological treatment with aldosterone antagonists [106]. Similarly, hypertension associated with secondary aldosteronism due to hyperparathyroidism resolves after parathyroidectomy [107,108].…”
Section: Calcium and Blood Pressure Regulationmentioning
confidence: 99%
“…H ypertension causes significant morbidity and mortality worldwide, having a prevalence of about 30 % of the adult world population, and around 85 % of them above 55 years-old (1,2). Hypertension has the largest prevalence of all cardiovascular risk factors and, due to its deleterious effects on the cardiovascular and renal systems, it is considered responsible for 45 % of the heart disease related deaths and 51 % of them due to stroke (1, 3).…”
Section: Discussionmentioning
confidence: 99%